Optimisation of Radar Navigation Equipment to Enhance Navigational Safety When Transiting Narrow Channels on Board MV. Tanto Mandiri - Edi Kurniawan; Diana Alia; Henna Nurdiansari; Sofyan Putra Wijaya (Meteor STIP Marunda, 2024)
Maritime transportation is a fundamental component of global and national logistics systems, particularly in archipelagic countries such as Indonesia, where sea routes provide essential connections between islands. Safe navigation relies heavily on the competence of ship personnel, especially officers responsible for navigational watchkeeping and situational awareness when operating in high-risk areas such as narrow channels. Increasing maritime traffic density in Indonesian waters has heightened the risk of navigational incidents, including collisions, particularly in restricted waterways where manoeuvring space is limited. This study aims to analyse strategies for optimising the use of Radar as a navigational aid to improve safety during narrow channel transits on board MV. Tanto Mandiri. A qualitative descriptive research approach was employed to examine the role of Radar utilisation, officer competency, and navigational practices in reducing collision risks. Data were collected through observations, interviews, and documentation related to shipboard navigation operations. The findings indicate that effective Radar utilisation is essential for supporting navigational decision-making, particularly in conditions of restricted visibility, adverse weather, and night-time operations when visual identification of navigational markers, such as buoys and lighthouse signals, becomes difficult. Radar provides critical information regarding vessel position, course, speed, distance from surrounding objects, and potential collision risks. However, the effectiveness of Radar as a safety tool depends significantly on the knowledge, skills, and operational awareness of navigating officers. Therefore, continuous training, familiarisation, and improvement of Radar operating competency among deck officers are required to maximise the benefits of electronic navigation equipment. Optimising Radar utilisation, combined with effective watchkeeping practices, can significantly reduce the likelihood of collisions and enhance navigational safety during narrow channel operations.